1999
DOI: 10.1023/a:1006267902186
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gossypol, a polyphenolic compound which depletes cellular energy by inhibition of several intracellular dehydrogenases, has been shown to have antiproliferative activity against human glial tumor cell lines in vitro and in nude mouse xenografts. Human trials of gossypol as a male contraceptive have demonstrated safety of long-term administration. We studied the activity of Gossypol 10 mg PO bid in 27 patients with pathologically confirmed glial tumors which had recurred after radiation therapy. Fifteen patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…Similar to this study, tissue culture studies in other cancer cell lines have shown that the (-) enantiomer of Gossypol has a more potent toxic effect than the (+) enantiomer [50,51]. While it has been reported that racemic gossypol is active against many cancer cell lines both in vitro and in vivo, it also generated toxic side effects in phase-1 clinical trials possibly due to the fact that it contains two aldehydes [52,53]. Therefore, attempts to produce less toxic derivatives of Gossypol that still retain the Bcl-2 inhibitory function have resulted in the synthesis of Apogossypol (2), which lacks the two aldehyde groups [54].…”
Section: Small Molecule Inhibitors Of Anti-apoptotic Bcl-2 Proteinssupporting
confidence: 79%
“…Similar to this study, tissue culture studies in other cancer cell lines have shown that the (-) enantiomer of Gossypol has a more potent toxic effect than the (+) enantiomer [50,51]. While it has been reported that racemic gossypol is active against many cancer cell lines both in vitro and in vivo, it also generated toxic side effects in phase-1 clinical trials possibly due to the fact that it contains two aldehydes [52,53]. Therefore, attempts to produce less toxic derivatives of Gossypol that still retain the Bcl-2 inhibitory function have resulted in the synthesis of Apogossypol (2), which lacks the two aldehyde groups [54].…”
Section: Small Molecule Inhibitors Of Anti-apoptotic Bcl-2 Proteinssupporting
confidence: 79%
“…For example, in a previous clinical study carried out in 23 patients with advanced refractory solid tumors, none of the patients showed evidence of tumor regression during treatment (73). A phase II trial of gossypol (10 mg orally twice daily) performed in 27 patients with pathologically confirmed recurrent glial tumors showed low treatment response and their plasma levels did not correlate well with response or toxicity (74). In another phase I/II study of 20 women with metastatic breast cancer refractory to doxorubicin and paclitaxel, the drug produced no therapeutic responses (75).…”
Section: Bcl2 Family Proteins (Bh3 Mimetics and Bcl-2 Antisense)mentioning
confidence: 97%
“…Studies have continued into more recent times with varying results involving different types of cancer. A selection of references is presented for some of the more promising clinical and preclinical trials [41][42][43], in addition to reports on preclinical studies on mice and rats [44][45][46].…”
Section: Anticancer Actionmentioning
confidence: 99%